Minority or minority? - Slobin, Mark (Puls – musik- och dansetnologisk tidskrift, 2023)
The articles in this journal issue cover a wide range of topics stimulated by the term “minority.” When I was first invited to consider this topic by my Swedish colleagues back in the 1980s and 1990s, I observed and described “multiculturalism” as a way a nation-state could control the definition of a swelling group of newcomers from other countries who came with very un-Scandinavian backgrounds and sensibilities. The work of Owe Ronström, Dan Lundberg, Krister Malm, and others showed that the invention and design of a “minority-music” establishment, with resources and performance structures, might have little to do with what the recent arrivals themselves thought of as their own intimate music (Ronström 1993, Lundberg, Malm & Ronström 2003, Ronström & Lundberg 2021). My impression is that even codified Scandinavian “folk music,” like modern European national languages, began more as a product of the Minority than as a grassroots movement.